The benefits of titling indigenous communities in the Peruvian Amazon: A stated preference approach - Allen Blackman; Sahan Dissanayake; Adan Martinez Cruz; Leonardo R. Corral; Maja Schling (Inter-American Development Bank (IDB), 2022)
We conduct a discrete choice experiment with leaders of a random sample of 164 Peruvian indigenous communities (ICs) - to our knowledge, the first use of rigorous stated preference methods to analyze land titling. We find that: (i) on average, IC leaders are willing to pay US35,000-45,000 for a title, roughly twice the per community administrative cost of titling; (ii) WTP is positively correlated with the value of IC land and the risk of land grabbing; and (iii) leaders prefer titling processes that involve indigenous representatives and titles that encompass land with cultural value.
Keywords: O13; Q15; C93; 330; discrete choice experiment; indigenous community; land rights; mixed multinomiallogit